(untitled) - R J Maddock (London, 1995)
The book provides a comprehensive course in modern electronics for engineering students. The first two chapters are introductory, describing basic concepts and passive components and devices. Chapter 3 develops the techniques of analysis used in the book including graphical methods, analysis by equivalent circuit techniques, analysis using phasor diagrams and complex algebra, frequency response analysis, transient analysis and digital analysis. The remaining chapters cover specific classes of electronic circuits: digital circuits, analogue circuits, waveform generation and conversion, analogue and digital conversion, power supplies and controlled rectifier systems
Keywords: electrical engineering,electronics